Peningkatan Hasil Belajar Matematika pada Materi Waktu Menggunakan Alat Peraga Waginem pada Peserta Didik Kelas II - Afriyani Afriyani; Irham Nugroho; Minzani Aufa (Paedagogie, 2023)
This research is motivied by the low mathematics learning outcomes in class II B MI Muhammadiyah Paremono, because the teacher uses the lecture method. The purpose of this study was to improve clock reading and writing skills with waginem props (morning and evening). The method used is Classroom Action Research (CAR) with the subject of class II B MI Muhammadiyah Paremono students for the 2021/2022 academic year. The final evaluation test instrument in this study was an evaluation test with 10 questions (essay). The research was conducted in two cycles. The indicators used are reading skills and writing skills. The results of the study show that waginem teaching aids can improve reading and writing skills so that student learning outcomes increase. This can be seen from the activities of the first cycle which showed the percentage of students' learning completeness was 75% with an average class of 87. Meanwhile in cycle II, the percentage of students' learning completeness was 100% with a class average of 96. Thus, the percentage of learning increased by 25%. Based on the results of the research conducted, it can be concluded that waginem teaching aids can improve mathematics learning outcomes in the time material at MI Muhammadiyah Paremono.